REVIEW ARTICLE: PEMANFAATAN MIKROKAPSUL ALGINAT SEBAGAI ADSORBEN ION LOGAM - Rumengan, Nur Khamillah; Panggabean, Aman Sentosa; P. Pasaribu, Subur; Lianasari, Ika Yekti (PROSIDING SEMINAR KIMIA, 2025)
A review article has been carried out on the use of alginate microcapsules as metal adsorbents. From the review of this article, it was found that metal pollution would harm the environment, so alginate microcapsules were made which have a carboxylic acid group, namely carboxyl which is able to bind with a metal. The metals that are adsorbed are Cd2+, Cu2+, Mn2+, Cr6+, Ni2+. The microcapsules reviewed in this article include Ca-Alginate-EDTA Microcapsules, Magnetite-Alginate Microcapsules (MNPs-ALG), Alginate and Alginate/ Montmorillonite Films, polyvinyl alcohol-Na-alginate Microcapsules, Ca-alginate-DMG. The aim of modifying alginate microcapsules is to increase the metal absorption capacity, metal absorption recovery and surface area of ​​each adsorbent. The way alginate microcapsules work is by exchanging unstable ions and the flow and stirring speed will affect the shape and size of the microcapsules. Slow stirring will produce microcapsules with a larger particle size because during the stirring process large droplets are formed. The absorption results obtained ranged from 84-119% and the adsorption capacity was 0.0301 - 185.95 mg/g. Keywords : Adsorption, Alginate, Metal Ions, Microcapsule